O professor de língua inglesa no ensino médio: normas, práticas e reflexões à luz do interacionismo sociodiscursivo - Araujo, Gerthrudes Hellena Cavalcante de (2014)
The performance of an English language teacher in high schools, as well as of any worker, is regulated by course plans, governmental rules, decisions of coordinators and school directors, among other guidelines. However, teachers are not mere reproducers of the norms, as they are professionals who reflect on all aspects of their practice in order to reconfigure it when appropriate (PERRENOUD, 2002; MEDRADO, 2008; BÁRBARA e RAMOS, 2009; PIMENTA e GHEDIN, 2012). Looking for representations of guidelines in the speech of high school English language teachers, this study investigates how mutual collaboration contributes to the definition and understanding of the praxeological dimension of the collective of professionals the teachers belong to. Taking oral texts produced in reflective sessions as corpus for analysis, the discussion proposed in this study is supported by the theories and methodologies from the Socio-discursive Interactionism (BRONCKART, 1999, 2006, 2008; MACHADO, BRONCKART, 2009), but it also considers the principles and concepts of the Clinic of Activity (CLOT, 2006; 2010), when discussing issues relating to the professional genre, collective work and guidelines. The discussion signals to the fact that the reflective attitude of the teachers participating in this research has contributed not only to reveal their representations in relation to their praxis, but also to their own continuing education and the strengthening of the collective of professionals.